EFFECTIVENESS MODEL OF MUNCAR PORT PUBLIC SERVICES: ANALYSIS OF PUBLIC SERVICE QUALITY - Tito Mariano Yesayabela; Aditya Tri Agustian; Ayu Wulandari Gunawan; Lunariana Lubis; Anma Sofyan Wahyudi (DIA: Jurnal Administrasi Publik, 2026)
Bureaucratic fragmentation in licensing poses a direct threat to the livelihoods of vulnerable fishermen at Muncar Port. A One-Stop Integrated Service (PTSP) model was implemented in 2021 to resolve this fragmentation. This study aims to quantitatively measure the effectiveness of this PTSP model from the user (fishermen) perspective. The research employed a quantitative descriptive design, surveying 30 fishermen selected via accidental sampling. Data was collected using a questionnaire structured on the five SERVQUAL dimensions (Tangibles, Reliability, Responsiveness, Assurance, Empathy) and analyzed using descriptive statistics. The findings indicate the model is only "fairly effective". While Reliability for simple administrative tasks is functional, the service is undermined by highly polarized Tangibles (good office aesthetics vs. poor functional access). Furthermore, results show significant deficits in Responsiveness (linked to technology adoption barriers), Assurance (lack of multi-jurisdictional staff competency), and Empathy (a "striking failure" in complaint handling). The study concludes that the PTSP achieves only moderate effectiveness, operating as a "technically proficient 'permit factory'" that remains fundamentally misaligned with its vulnerable user base and fails in the critical human dimensions of service.